1994
DOI: 10.1007/bf01229077
|View full text |Cite
|
Sign up to set email alerts
|

A case of appendiceal cancer metastatic to the stomach with pseudomyxoma peritonei

Abstract: Appendiceal cancer associated with pseudomyxoma peritonei is a low grade malignancy and its extraperitoneal metastasis is extremely rare. We report a case of gastric metastasis of this tumor in a 76-year-old man. Two metastatic gastric tumors, which appeared after a 1-year interval, were successfully resected endoscopically. The patient was well for more than 3 years after the onset of the disease. To our knowledge, gastric metastasis from appendiceal cancer with pseudomyxoma peritonei has not been previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Metastatic gastric tumors may originate from various organs [9, 10, 11, 12, 13, 14, 15, 16, 17] but are most common from breast, lung, and esophageal cancers and melanoma [4, 5]. Oda et al reported that malignant melanoma was the most common tumor to metastasize to the stomach [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metastatic gastric tumors may originate from various organs [9, 10, 11, 12, 13, 14, 15, 16, 17] but are most common from breast, lung, and esophageal cancers and melanoma [4, 5]. Oda et al reported that malignant melanoma was the most common tumor to metastasize to the stomach [5].…”
Section: Discussionmentioning
confidence: 99%
“…Pector et al reported a patient who had been alive more than 6 years after subtotal gastrectomy for MGT from malignant melanoma [31]. Less invasive treatment, such as endoscopic resection of the MGT, was reported to be feasible for renal cell carcinoma [10] and appendiceal cancer [12]. Saito et al suggested that surgical resection be performed when an MGT from esophageal cancer is limited to the stomach and is < 2 cm because the mean survival time after treatment for MGT is extremely short [7].…”
Section: Discussionmentioning
confidence: 99%
“…Miyashita et al 13 reported the first case of appendiceal cancer with psudomyxoma peritonei that metastasized to the stomach. The tumor was endoscopically removed and diagnosed.…”
Section: Discussionmentioning
confidence: 98%
“…Only 12 cases of distant metastasis have been reported. [11][12][13][14][15][16] These include pleural metastasis with invasion of the thoracic wall; invasion of the pleural cavities, possibly due to spread through a diaphragmatic defect; pulmonary metastasis; invasion of an axillary lymph node; subcutaneous localization in the thoracic wall; metastasis in the periaortic lymph node; metastasis in the liver, pancreas, urinary bladder, periaortic lymph node, pleura, and pericardium; two cases of metastasis in the spleen; metastasis in the brain and lung; metastasis in the diaphragm, liver, gallbladder, spleen, and kidney; and metastasis in the stomach. The lymph nodes, lungs, spleen, and liver are possible metastatic sites, and both hematogenous metastasis and lymphatic metastasis have been considered possible.…”
Section: Discussionmentioning
confidence: 99%
“… 3 However, metastatic primary appendiceal cancer to the GI tract is rare, and only two cases of gastric metastases have been reported. 4 5 However, small bowel metastases caused by primary appendiceal cancer have never been reported in the literature. Our patient had histologically proven small intestinal lesions originating from primary appendiceal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%